(untitled) (Bangladesh Journal of Medical Microbiology, 2021)
Background: The COVID-19 pandemic is already a public health emergency and led to millions of cases and deaths worldwide since its outbreak on December 2019. Public health responses is not seen to identify asymptomatic individuals who are also infectious. Data are also limited on the duration of viral clearance. Methods: Retrospectively and randomly selected 2117 cases who came to do PCR for COVID-19 in Novus molecular Lab, Dhaka between 5 March 2021 and 5 May 2021. Laboratory data and patient’s characteristics, such as age, sex, and other relevant history were collected from our laboratory database. Results: Among 2117 cases (symptomatic or asymptomatic patients), SARS_CoV_2 RNA was detected in 501 samples (24%). Among 501 positive cases 352 were male and 149 were female with the mean age of 34.81 (SD±12). The most common complaints were fatigue (68%), high temperature (57%); but anosmia and ageusia were present among 57% cases in symptomatic and also asymptomatic groups. Among the positive cases, 30-39 years of age group was mostly affected followed by 19-29 years. 48% asymptomatic cases were found among the positive cases. The mean CT value was significantly higher in asymptomatic (24.5 ± 0.4), compared to symptomatic (23.37± 0.3). The median duration of viral conversion in this study was 20 days (IQR 16–33 days). Conclusion: We found those people having symptoms have delayed viral clearance. These data disclose the high asymptomatic incidence of SARS-CoV-2 infection in Bangladesh, and that these cases may act as carrier. Public health expert should think for routine screening in office or other area to identify asymptomatic cases and to contain the outbreak. Bangladesh J Med Microbiol 2021; 15 (1): 3-7